Ultrahigh-nickel single-crystal positive electrode material as well as preparation method and application thereof

By introducing flux and high-priced doping elements into ultra-high nickel single-crystal positive electrode materials, doping amounts are solved, and the formation of small-particle-sized single crystals and the improvement of high kinetic performance are achieved.

CN119581549AInactive Publication Date: 2025-03-07TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202510138848.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Ultra-high nickel single crystal positive electrode materials require high temperature and long-term annealing during the synthesis process, resulting in high sintering temperature, Li/Ni mixed discharge and oxygen loss, affecting electrochemical performance.

Method used

The flux doping elements and high-valent doping elements are introduced, and the doping amounts of both are formulated by establishing a relationship between the flux doping amount and the high-valent doping amount, forming a single crystal with a small particle size and uniform dispersion, reducing the sintering temperature and improving the kinetic performance.

Benefits of technology

It achieves a stable single crystal morphology at a lower synthesis temperature, reduces Li+ diffusion path, improves dynamic performance, and gives full play to the advantages of high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581549A_ABST
    Figure CN119581549A_ABST
Patent Text Reader

Abstract

The invention provides an ultrahigh-nickel single-crystal positive electrode material and a preparation method and application thereof.The ultrahigh-nickel single-crystal positive electrode material comprises fluxing agent doping elements and high-valence doping elements, the fluxing agent doping elements comprise Zr, Ce, Sr, Y, La, Sn or Na, and the high-valence doping elements comprise Sb, W, Nb, Ta, Mo, Ti or P; the doping amount of the fluxing agent doping element is omega A, the doping amount of the high-valence doping element is omega B, and omega A and omega B meet the following relational expression: 0.5 < 0.746 * exp [-omega B / (0.891 * omega A)] + 0.556 < 1.0. Omega A and Omega B meet a specific relational expression, two doping elements are effectively promoted to play a role, a small-particle-size and uniformly-dispersed single crystal is formed, the material has high stability and safety of the single crystal, a Li < + > diffusion path can be shortened, dynamics can be improved, and the advantage of high capacity can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to an ultra-high nickel single crystal positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of lithium-ion batteries in new energy electric vehicles, range anxiety and safety issues are the main challenges facing lithium-ion batteries. Ultra-high nickel ternary cathode materials have the advantages of high energy density, low cost and high safety, and are considered to be one of the most promising next-generation lithium-ion battery cathodes. Among them, single-crystal ultra-high nickel cathode materials have excellent structure, safety performance and cycle stability, and have attracted widespread attention in recent years. This is mainly because they do not have grain boundaries, have uniform lattice orientation and orderly crystal plane arrangement, effectively reduce interfacial reactions and microcracks, and have the advantages of high mechanical strength and high compaction density.

[0003] However, the preparation of ultra-high nickel single crystal cathode materials often requires a higher calcination temperature to promote grain growth and grain boundary melting. However, as the Ni content increases, the higher the calcination temperature, the more likely it is to cause serious Li / Ni mixing and irreversible oxygen loss, thereby leading to the deterioration of electrochemical performance. However, if the sintering temperature is low, it will not promote grain boundary cracking to form a single crystal morphology with good dispersion, but will form a polycrystalline morphology with primary particle agglomeration. In addition, the single crystal material has a larger grain size, which leads to Li + The long diffusion path makes Li + The diffusion kinetics are relatively slow, which will lead to uneven lithium concentration distribution during the cycle process. With the increase of Ni content and current density in the positive electrode, this trend will be further aggravated, resulting in the coexistence of H2 and H3 phases in a single particle. The resulting non-uniform strain and stress will produce structural defects and cause intracrystalline cracks, ultimately resulting in more serious structural degradation and performance deterioration.

[0004] Therefore, ultra-high nickel materials require a lower calcination temperature to maintain structural stability, while the synthesis of single crystals requires high temperature and long annealing. How to form single crystal morphology and maintain structural stability at a lower synthesis temperature, and control the primary particle size within an appropriate range to shorten the Li + Diffusion path enhancement kinetics is a technical problem that needs to be urgently solved in ultra-high nickel single crystal positive electrode materials. Summary of the invention

[0005] The purpose of the present invention is to provide an ultra-high nickel single crystal positive electrode material and a preparation method and application thereof. The ultra-high nickel single crystal positive electrode material introduces a flux doping element to solve the problem of high material synthesis temperature and introduces a high-priced doping element that inhibits grain growth, thereby reducing the grain size. A relationship between the doping amount of the flux doping element and the doping amount of the high-priced element is established, which effectively promotes the two doping elements to play a role, forms a single crystal with a small particle size and uniform dispersion, and enables the ultra-high nickel single crystal positive electrode material to have both high stability and safety of the single crystal and shorten the Li + Diffusion path, improves kinetic performance, and takes advantage of high capacity.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an ultra-high nickel single crystal positive electrode material, the ultra-high nickel single crystal positive electrode material comprising a flux doping element and a high-valent doping element, the flux doping element comprising any one of Zr, Ce, Sr, Y, La, Sn or Na or a combination of at least two thereof, the high-valent doping element comprising any one of Sb, W, Nb, Ta, Mo, Ti or P or a combination of at least two thereof;

[0008] The doping amount of the flux doping element is ω A , the doping amount of the high-valent doping element is ω B , the ω A and ω B Satisfies the following relationship:

[0009] 0.5<0.746×exp[-ω B / (0.891×ω A )]+0.556<1.0.

[0010] The present invention introduces flux doping elements into the ultra-high nickel single crystal positive electrode material to reduce the surface energy of the crystal plane, promote grain growth, accelerate grain boundary fusion to form a single crystal morphology, thereby reducing the sintering temperature of the material, reducing Li / Ni mixing, and stabilizing lattice oxygen, thereby solving the problem of high synthesis temperature of ultra-high nickel single crystal positive electrode material. However, the addition of flux will promote grain growth, making the primary particle size of the material larger, and will also bring about Li + The disadvantage of diffusion dynamics hysteresis causes the capacity to decrease. Based on this, the present invention introduces high-price doping elements that inhibit grain growth while introducing flux doping elements, reduces the grain size, and establishes the doping amount ω of the flux doping elements. A and the doping amount of the high-valent doping element ω BThe relationship between the two is used to adjust the doping amount of the two, which effectively promotes the synergistic effect of the two, forming a single crystal with small particle size and uniform dispersion, so that the ultra-high nickel single crystal positive electrode material has both the high stability and safety of the single crystal and can shorten the Li + The diffusion path improves the kinetics and takes advantage of the high capacity.

[0011] 0.5<0.746×exp[-ω B / (0.891×ω A )]+0.556<1.0, for example, it can be 0.51, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 0.99, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 0.55-0.85.

[0012] Preferably, the ω A It is 500-2000ppm, for example, it can be 500ppm, 700ppm, 900ppm, 1100ppm, 1300ppm, 1500ppm, 1700ppm, 1900ppm or 2000ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Preferably, the ω B It is 1000-3000ppm, for example, it can be 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm, 2200ppm, 2400ppm, 2600ppm, 2800ppm or 3000ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] The doping amount of the flux doping element of the present invention is A and the doping amount of the high-valent doping element ω B On the basis of satisfying the above relationship, it is preferable that the above range is used to further promote the synergistic effect of the flux doping element and the high-valent doping element.

[0015] Further preferably, the flux doping element is any one of Zr, Ce, Sr or Sn, or a combination of at least two of them.

[0016] Further preferably, the high-valent doping element is any one of Sb, W, Nb or Mo, or a combination of at least two of them.

[0017] Preferably, the ultra-high nickel single crystal positive electrode material further comprises a matrix, the chemical formula of which is Li x Ni aCo b Mn 1-a-b O2, wherein 1.02≤x≤1.08, for example, it can be 1.02, 1.03, 1.04, 1.05, 1.06, 1.07 or 1.08, 0.95≤a<1, for example, it can be 0.95, 0.96, 0.97, 0.98 or 0.99, 0<b≤0.04, for example, it can be 0.005, 0.01, 0.02, 0.03 or 0.04, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] The doping of flux doping elements and high-valent doping elements and the relationship between the doping amounts of the two elements described in the present invention are applicable to ultra-high nickel single crystal positive electrode materials, in which 0.95≤a<1 in the matrix of the ultra-high nickel single crystal positive electrode materials.

[0019] Preferably, the ultra-high nickel single crystal positive electrode material also includes a coating element or a coated solid electrolyte, and the coating element includes any one or a combination of at least two of Co, Al, W, F, Li, Ce, B, Ti, Se, Si or Zr.

[0020] Preferably, the primary particle size of the ultra-high nickel single crystal positive electrode material is 0.6-0.8 μm, for example, it can be 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm or 0.8 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In a second aspect, the present invention provides a method for preparing the ultra-high nickel single crystal positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0022] The ultra-high nickel precursor material, flux, high-valent element dopant and lithium source are mixed and sintered once to obtain the ultra-high nickel single crystal positive electrode material.

[0023] The flux doping element and the high-valent doping element of the present invention are obtained by mixing and sintering a precursor with a corresponding dopant and a lithium source to achieve doping of the doping element.

[0024] Preferably, the primary sintering is first carried out at a heating rate of 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min, to 450-550°C, such as 450°C, 500°C or 550°C, and kept warm for 5-10h, such as 5h, 7h, 9h or 10h, and then at a heating rate of 1-3°C / min, such as 1°C / min, 2°C / min or 3°C / min, to 700-750°C, such as 700°C, 720°C, 740°C or 750°C, and kept warm for 8-15h, such as 8h, 10h, 12h, 14h or 15h. However, the present invention is not limited to the values ​​listed, and other values ​​not listed within the numerical range are also applicable.

[0025] The sintering temperature of the ultra-high nickel single crystal positive electrode material of the present invention is relatively low, and a single crystal material with small particle size and high dispersibility can also be obtained.

[0026] Preferably, the primary sintering atmosphere is a pure oxygen atmosphere.

[0027] Preferably, the primary sintering is followed by a crushing and screening step.

[0028] Preferably, after the primary sintering, the primary sintered material is mixed with a coating source and sintered for a secondary time to obtain the ultra-high nickel single crystal positive electrode material.

[0029] The ultra-high nickel single crystal positive electrode material of the present invention is also coated, which can further improve the stability and electrochemical performance of the material.

[0030] Preferably, the secondary sintering temperature is 300-600°C, for example, 300°C, 400°C, 500°C or 600°C, the time is 5-10h, for example, 5h, 7h, 9h or 10h, the heating rate is 3-5°C / min, for example, 3°C / min, 4°C / min or 5°C / min, and the sintering atmosphere is a pure oxygen atmosphere.

[0031] Preferably, after the secondary sintering, the temperature is cooled to room temperature at a cooling rate of 3-5°C / min, for example, 3°C / min, 4°C / min or 5°C / min, and sieved to obtain the ultra-high nickel single crystal positive electrode material.

[0032] Preferably, the coating source includes any one of a Co source, an Al source, a W source, a F source, a Li source, a Ce source, a B source, a Ti source, a Se source, a Si source, a Zr source or a solid electrolyte, or a combination of at least two thereof.

[0033] Preferably, the added amount of the coating source is 0.02-1.5wt% of the primary sintering material, for example, it can be 0.02wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the ultra-high nickel single crystal positive electrode material as described in the first aspect.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The present invention introduces flux doping elements into the ultra-high nickel single crystal positive electrode material to solve the problem of high synthesis temperature of the ultra-high nickel single crystal positive electrode, and at the same time introduces high-priced doping elements that inhibit grain growth to reduce the grain size and shorten the Li + diffusion path, improve kinetics, and establish the doping amount of flux doping elements ω A and the doping amount of the high-valent doping element ω B The relationship between the two doping elements is used to adjust the doping amount of the two doping elements, which effectively promotes the synergistic effect of the two elements to form a single crystal with small particle size and uniform dispersion, so that the ultra-high nickel single crystal positive electrode material has both the high stability and safety of the single crystal and can shorten the Li + Diffusion path, improves kinetic performance, and takes advantage of high capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a SEM image of the ultra-high nickel single crystal positive electrode material described in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0039] Example 1

[0040] This embodiment provides an ultra-high nickel single crystal positive electrode material, the ultra-high nickel single crystal positive electrode material includes a matrix, a flux doping element, a high-valent doping element and a coating element, the flux doping element is Zr, the high-valent doping element is Sb, the coating element is Al, and the matrix is ​​Li 1.05 Ni 0.96 Co 0.02 Mn 0.02 O2;

[0041] The doping amount of the flux doping element is ω A , the doping amount of the high-valent doping element is ωB , the ω A and ω B Satisfies the following relationship: 0.746×exp[-ω B / (0.891×ω A )]+0.556=0.72, where ω A 1500ppm,ω B 2000ppm;

[0042] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.69 μm;

[0043] The method for preparing the ultra-high nickel single crystal positive electrode material comprises the following steps:

[0044] (1) According to the formula, the ultra-high nickel precursor material, flux, high-valent element dopant and lithium hydroxide are mixed, and then in a pure oxygen atmosphere, the temperature is first increased to 500°C at a heating rate of 3°C / min, and kept at this temperature for 8 hours, and then the temperature is increased to 720°C at a heating rate of 2°C / min, and kept at this temperature for 10 hours, and finally the temperature is lowered to room temperature at a rate of 4°C / min, and then the primary sintering material is obtained after being crushed and sieved;

[0045] Wherein, the ultra-high nickel precursor material is Ni 0.96 Co 0.02 Mn 0.02 (OH)2, the flux is zirconium oxide, and the high-valent element dopant is antimony pentoxide;

[0046] (2) Mixing the primary sintered material of step (1) with a coating source, wherein the coating source is alumina, and the amount of the coating source added is 1wt% of the primary sintered material, and then heating to 400°C at a heating rate of 4°C / min in a pure oxygen atmosphere, keeping the temperature for 8h, and then cooling to room temperature at a rate of 4°C / min. After sieving, the ultra-high nickel single crystal positive electrode material is obtained. The SEM image of the ultra-high nickel single crystal positive electrode material is as shown in Figure 1 As shown by Figure 1 It can be seen that the primary particles of the material have a small particle size and are dispersed uniformly.

[0047] Example 2

[0048] This embodiment provides an ultra-high nickel single crystal positive electrode material, which includes a matrix, a flux doping element, a high-valent doping element and a coating element, wherein the flux doping element is Ce, the high-valent doping element is W, the coating element is Co, and the matrix is ​​Li 1.06 Ni 0.95 Co 0.04 Mn 0.01 O2;

[0049] The doping amount of the flux doping element is ω A , the doping amount of the high-valent doping element is ω B , the ω A and ω B Satisfies the following relationship: 0.746×exp[-ω B / (0.891×ω A )]+0.556=0.56, where ω A 500ppm,ω B 3000ppm;

[0050] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.53 μm;

[0051] The method for preparing the ultra-high nickel single crystal positive electrode material comprises the following steps:

[0052] (1) According to the formula, the ultra-high nickel precursor material, flux, high-valent element dopant and lithium hydroxide are mixed, and then in a pure oxygen atmosphere, the temperature is first increased to 450°C at a heating rate of 2°C / min, and kept at this temperature for 10 hours, and then the temperature is increased to 700°C at a heating rate of 1°C / min, and kept at this temperature for 15 hours, and finally the temperature is lowered to room temperature at a rate of 3°C / min, and then the mixture is crushed and sieved to obtain a primary sintering material;

[0053] Wherein, the ultra-high nickel precursor material is Ni 0.95 Co 0.04 Mn 0.01 (OH)2, the flux is cerium oxide, and the high-valent element dopant is tungsten oxide;

[0054] (2) Mixing the primary sintered material of step (1) with a coating source, wherein the coating source is hydroxycobalt, and the amount of the coating source added is 0.02wt% of the primary sintered material, and then heating to 600°C at a heating rate of 5°C / min in a pure oxygen atmosphere, keeping the temperature for 5h, and then cooling to room temperature at a rate of 3°C / min, and sieving to obtain the ultra-high nickel single crystal positive electrode material.

[0055] Example 3

[0056] This embodiment provides an ultra-high nickel single crystal positive electrode material, the ultra-high nickel single crystal positive electrode material includes a matrix, a flux doping element, a high-valent doping element and a coating element, the flux doping element is Zr, the high-valent doping element is Sb, the coating element is Al, and the matrix is ​​Li 1.05 Ni 0.96 Co 0.02 Mn 0.02 O2;

[0057] The doping amount of the flux doping element is ωA , the doping amount of the high-valent doping element is ω B , the ω A and ω B Satisfies the following relationship: 0.746×exp[-ω B / (0.891×ω A )]+0.556=0.8, where ω A 2000ppm,ω B 1000ppm;

[0058] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.77 μm;

[0059] The method for preparing the ultra-high nickel single crystal positive electrode material comprises the following steps:

[0060] (1) According to the formula, the ultra-high nickel precursor material, flux, high-valent element dopant and lithium hydroxide are mixed, and then in a pure oxygen atmosphere, the temperature is first increased to 550°C at a heating rate of 5°C / min, and kept at this temperature for 5 hours, and then the temperature is increased to 750°C at a heating rate of 3°C / min, and kept at this temperature for 8 hours, and finally the temperature is lowered to room temperature at a rate of 5°C / min, and then the primary sintering material is obtained after being crushed and sieved;

[0061] Wherein, the ultra-high nickel precursor material is Ni 0.96 Co 0.02 Mn 0.02 (OH)2, the flux is zirconium oxide, and the high-valent element dopant is antimony pentoxide;

[0062] (2) Mixing the primary sintered material of step (1) with a coating source, wherein the coating source is alumina and the amount of the coating source added is 1.5wt% of the primary sintered material, then heating to 300°C at a heating rate of 3°C / min in a pure oxygen atmosphere, keeping the temperature for 10 hours, then cooling to room temperature at a rate of 5°C / min, and sieving to obtain the ultra-high nickel single crystal positive electrode material.

[0063] Example 4

[0064] This embodiment provides an ultra-high nickel single crystal positive electrode material. A is 300ppm, 0.746×exp[-ω B / (0.891×ω A )]+0.556=0.556, the rest are the same as those in Example 1.

[0065] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.53 μm;

[0066] The method for preparing the ultra-high nickel single crystal positive electrode material is the same as that of Example 1 except that the amount of flux added during the primary sintering is adaptively changed.

[0067] Example 5

[0068] This embodiment provides an ultra-high nickel single crystal positive electrode material. A is 2500ppm, 0.746×exp[-ω B / (0.891×ω A )]+0.556=0.86, the rest are the same as those in Example 1.

[0069] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.82 μm;

[0070] The method for preparing the ultra-high nickel single crystal positive electrode material is the same as that of Example 1 except that the amount of flux added during the primary sintering is adaptively changed.

[0071] Example 6

[0072] This embodiment provides an ultra-high nickel single crystal positive electrode material. B is 800ppm, 0.746×exp[-ω B / (0.891×ω A )]+0.556=0.97, the rest are the same as those in Example 1.

[0073] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.92 μm;

[0074] The preparation method of the ultra-high nickel single crystal positive electrode material is the same as that of Example 1 except that the amount of the high-valent element dopant added during the primary sintering is adaptively changed.

[0075] Example 7

[0076] This embodiment provides an ultra-high nickel single crystal positive electrode material. B is 3500ppm, 0.746×exp[-ω B / (0.891×ω A )]+0.556=0.61, the rest are the same as those in Example 1.

[0077] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.57 μm;

[0078] The preparation method of the ultra-high nickel single crystal positive electrode material is the same as that of Example 1 except that the amount of the high-valent element dopant added during the primary sintering is adaptively changed.

[0079] Example 8

[0080] The present embodiment provides an ultra-high nickel single crystal positive electrode material. The ultra-high nickel single crystal positive electrode material is the same as that of the first embodiment except that in the preparation method thereof, the temperature is raised to 650° C. at a heating rate of 2° C. / min and kept warm for 10 h to allow the obtained ultra-high nickel single crystal positive electrode material to adapt.

[0081] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.35 μm.

[0082] Example 9

[0083] The present embodiment provides an ultra-high nickel single crystal positive electrode material. The ultra-high nickel single crystal positive electrode material is the same as that in the preparation method thereof, except that in step (1), the temperature is raised to 800° C. at a heating rate of 2° C. / min and kept warm for 10 h to allow the obtained ultra-high nickel single crystal positive electrode material to adapt to changes.

[0084] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.97 μm.

[0085] Comparative Example 1

[0086] This comparative example provides an ultra-high nickel single crystal positive electrode material, which is the same as Example 1 except that the ultra-high nickel single crystal positive electrode material is not doped with flux doping elements.

[0087] The primary particle size of the ultra-high nickel single crystal positive electrode material is 0.51 μm.

[0088] The preparation method of the ultra-high nickel single crystal positive electrode material is the same as that of Example 1 except that no flux is added during the primary sintering.

[0089] Comparative Example 2

[0090] This comparative example provides an ultra-high nickel single crystal positive electrode material, which is the same as Example 1 except that the ultra-high nickel single crystal positive electrode material is not doped with high-valent doping elements.

[0091] The primary particle size of the ultra-high nickel single crystal positive electrode material is 1.12 μm.

[0092] The preparation method of the ultra-high nickel single crystal positive electrode material is the same as that of Example 1 except that no high-valent element dopant is added during the primary sintering.

[0093] Comparative Example 3

[0094] This comparative example provides an ultra-high nickel single crystal positive electrode material. Bis 500ppm, 0.746×exp[-ω B / (0.891×ω A )]+0.556=1.1, the rest are the same as those in Example 1.

[0095] The primary particle size of the ultra-high nickel single crystal positive electrode material is 1.06 μm.

[0096] The preparation method of the ultra-high nickel single crystal positive electrode material is the same as that of Example 1 except that the amount of the high-valent element dopant added during the primary sintering is adaptively changed.

[0097] In the above embodiments and comparative examples, ω A ,ω B and 0.746×exp[-ω B / (0.891×ω A )]+0.556 as shown in Table 1; the ultra-high nickel single crystal positive electrode material described in the above embodiments and comparative examples is evenly mixed with a conductive agent and a binder and then coated on an aluminum foil. After drying, tabletting and slicing, a battery is assembled in an argon-protected glove box, wherein the negative electrode of the battery is a metal lithium sheet, the diaphragm is a polyethylene microporous diaphragm, and the electrolyte is 1MLiPF6-EC / DMC (the volume ratio of EC and DMC is 1:1); the battery is subjected to a capacity test (2.8-4.3V, 0.1C) and a cycle performance test (3.0-4.5V, 0.5C / 1C) and the test results are shown in Table 1:

[0098] Table 1

[0099]

[0100] From Table 1 we can see that:

[0101] It can be seen from Examples 1-3 and Comparative Examples 1-3 that the flux doping element and the high-price doping element of the present invention need to be doped at the same time, and the doping amount needs to satisfy a certain relationship, while solving the problem of high synthesis temperature of ultra-high nickel single crystal positive electrode and solving the problem of Li + The problem of a long diffusion path; from Examples 1 and 4-7, it can be seen that the doping amount of the flux doping element and the doping amount of the high-price doping element will affect 0.746×exp[-ω B / (0.891×ω A )]+0.556, which will affect the synergistic effect of the flux doping elements and the high-valent doping elements, and affect the performance of the lithium-ion battery; it can be seen from Examples 1 and 8-9 that after the present invention is doped with a specific element, a corresponding sintering temperature needs to be matched with it. Therefore, the maximum temperature of the primary sintering of the present invention is within the preferred range, which can further improve the electrochemical properties of the ultra-high nickel single crystal positive electrode material.

[0102] In summary, the present invention provides an ultra-high nickel single crystal positive electrode material and a preparation method and application thereof. The ultra-high nickel single crystal positive electrode material solves the problem of high material synthesis temperature by introducing flux doping elements, and at the same time introduces high-priced doping elements that inhibit grain growth, reduces grain size, and establishes a relationship between the doping amount of the flux doping element and the doping amount of the high-priced element, effectively promoting the two doping elements to play a role, forming a small-sized and uniformly dispersed single crystal, so that the ultra-high nickel single crystal positive electrode material has both high stability and safety of the single crystal, and can shorten the Li + Diffusion path, improves kinetic performance, and takes advantage of high capacity.

[0103] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. An ultra-high nickel single crystal positive electrode material, characterized in that: The ultra-high nickel single crystal positive electrode material includes a flux doping element and a high-valent doping element, wherein the flux doping element includes any one of Zr, Ce, Sr, Y, La, Sn or Na or a combination of at least two thereof, and the high-valent doping element includes any one of Sb, W, Nb, Ta, Mo, Ti or P or a combination of at least two thereof; The doping amount of the flux doping element is ω A , the doping amount of the high-valent doping element is ω B , the ω A and ω B Satisfies the following relationship: 0.5<0.746×exp[-ω B / (0.891×ω A )]+0.556<1.

0.

2. The ultra-high nickel single crystal positive electrode material according to claim 1, characterized in that: The ω A 500-2000ppm; And / or, the ω B 1000-3000ppm; and / or, 0.55≤0.746×exp[-ω B / (0.891×ω A )]+0.556≤0.

85.

3. The ultra-high nickel single crystal positive electrode material according to claim 1 or 2, characterized in that: The flux doping element is any one of Zr, Ce, Sr or Sn or a combination of at least two thereof; And / or, the high-valent doping element is any one of Sb, W, Nb or Mo, or a combination of at least two thereof.

4. The ultra-high nickel single crystal positive electrode material according to claim 1 or 2, characterized in that: The ultra-high nickel single crystal positive electrode material also includes a matrix, the chemical formula of which is Li x Ni a Co b Mn 1-a-b O2, where 1.02≤x≤1.08, 0.95≤a<1, 0<b≤0.04; And / or, the ultra-high nickel single crystal positive electrode material further includes a coating element or a coated solid electrolyte, wherein the coating element includes any one or a combination of at least two of Co, Al, W, F, Li, Ce, B, Ti, Se, Si or Zr; And / or, the primary particle size of the ultra-high nickel single crystal positive electrode material is 0.6-0.8 μm.

5. A method for preparing the ultra-high nickel single crystal positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The ultra-high nickel precursor material, flux, high-valent element dopant and lithium source are mixed and sintered once to obtain the ultra-high nickel single crystal positive electrode material.

6. The preparation method according to claim 5, characterized in that: The primary sintering is first heated to 450-550°C at a heating rate of 2-5°C / min, kept warm for 5-10h, then heated to 700-750°C at a heating rate of 1-3°C / min, kept warm for 8-15h; And / or, the primary sintering atmosphere is a pure oxygen atmosphere; And / or, the primary sintering is followed by a crushing and screening step.

7. The preparation method according to claim 5, characterized in that: After the primary sintering, the primary sintered material is mixed with a coating source and sintered for a secondary time to obtain the ultra-high nickel single crystal positive electrode material.

8. The preparation method according to claim 7, characterized in that: The secondary sintering temperature is 300-600°C, the time is 5-10h, the heating rate is 3-5°C / min, and the sintering atmosphere is pure oxygen atmosphere; And / or, after the secondary sintering, the material is cooled to room temperature at a rate of 3-5°C / min and sieved to obtain the ultra-high nickel single crystal positive electrode material.

9. The preparation method according to claim 7 or 8, characterized in that: The coating source includes any one of a Co source, an Al source, a W source, a F source, a Li source, a Ce source, a B source, a Ti source, a Se source, a Si source, a Zr source or a solid electrolyte, or a combination of at least two thereof; And / or, the added amount of the coating source is 0.02-1.5wt% of the primary sintering material.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the ultra-high nickel single crystal positive electrode material as described in any one of claims 1-4.

Citation Information

Patent Citations

  • Preparation method of single-crystal nickel cobalt lithium manganate ternary material

    CN113299905A

  • Composite doped high-nickel large-single-crystal ternary layered oxide positive electrode material and preparation method and application thereof

    CN115763749A

  • High-nickel single-crystal positive electrode material as well as preparation method and application thereof

    CN116553627A

  • Multistage blended ternary positive electrode material and preparation method and application thereof

    CN116960309A

  • Sodium-ion battery positive electrode material with low residual alkali, preparation method and sodium-ion battery

    CN116986649A

Cited By

  • Positive pole piece, battery, energy storage device and electric equipment

    CN121483982A

  • Positive electrode sheet, battery, energy storage device, and electric device

    CN121483982B

  • High-nickel positive electrode material, preparation method thereof, positive electrode, secondary battery, and electric device

    CN122619713A